The superior mesenteric artery syndrome with chronic diarrhoea as presentation - Abd Rahim, Ezamin; Bahari, Norafida; Abu Hassan, Hasyma; Suppiah, Subapriya; Mohamad Saini, Suraini (Community Health Society Malaysia (CHSM), 2015)
Summary Superior mesenteric artery (SMA) syndrome is rare and potentially life-treatening gastro-vascular disorder which also known as Wilkie’s syndrome, cast syndrome, mesenteric root syndrome, chronic duodenal ileus and intermittent arterio-mesenteric occlusion. Signs and symptoms include nausea, vomiting, postprandial abdominal pain, diarrhoea, reflux and heartburn. We report such a case of SMA syndrome which presented as chronic diarrohea as symptom which lead to malabsorption and loss of retroperitoneal fat and causing the SMA syndrome.